2011
DOI: 10.1097/ccm.0b013e3182120cb8
|View full text |Cite|
|
Sign up to set email alerts
|

Ascorbic acid attenuates lipopolysaccharide-induced acute lung injury*

Abstract: Ascorbic acid administered in an interventional manner following lipopolysaccharide infusion attenuates proinflammatory, procoagulant states that induce lung vascular injury in an animal model of sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(169 citation statements)
references
References 41 publications
7
156
2
4
Order By: Relevance
“…Also, bolus injection of ascorbate or DHAA (200 mg/kg) decreases the concentration of protein in bronchoalveolar lavage fluid of LPS-exposed mice (17). Prevention by vitamin C of LPSinduced endothelial barrier dysfunction is a likely explanation for these findings.…”
Section: Extravasation Of Plasma Proteins and Fluidmentioning
confidence: 74%
See 3 more Smart Citations
“…Also, bolus injection of ascorbate or DHAA (200 mg/kg) decreases the concentration of protein in bronchoalveolar lavage fluid of LPS-exposed mice (17). Prevention by vitamin C of LPSinduced endothelial barrier dysfunction is a likely explanation for these findings.…”
Section: Extravasation Of Plasma Proteins and Fluidmentioning
confidence: 74%
“…Injection of DHAA (i.e., the oxidized state of vitamin C that cells take up and reduce to ascorbate) (200 mg/kg) also prolongs survival in FIP mice (18). Similarly, injection of ascorbate or DHAA (200 mg/kg) increases survival in mice made endotoxemic by exposure to LPS (17).…”
Section: Mortality and Morbiditymentioning
confidence: 99%
See 2 more Smart Citations
“…In our pre-clinical studies, we showed that parenteral infusion of ascorbic acid (200 mg/kg) could attenuate sepsis induced organ injury in wild type mice [2,3] and in vitamin C knockout mice (lacking L-gulono-γ-lactone oxidase, Gulo) [4]. In these studies parenteral ascorbic acid was effective at reducing mortality and sepsis-induced organ injury through pleiotropic mechanisms including down-regulation of pro-inflammatory mediator secretion, normalization of coagulopathy, improved alveolar fluid clearance and enhanced alveolar epithelial barrier function.…”
Section: Introductionmentioning
confidence: 99%